ATP-binding to P-type ATPases as revealed by biochemical, spectroscopic, and crystallographic experiments - Kubala, Martin (Proteins, 2006)
P-type ATPases form a large family of cation translocating ATPases. Recent progress in crystallography yielded several high-resolution structures of Ca(2+)-ATPase from sarco(endo)plasmic reticulum (SERCA) in various conformations. They could elucidate the conformational changes of the enzyme, which are necessary for the translocation of cations, or the mechanism that explains how the nucleotide binding is coupled to the cation transport. However, crystals of proteins are usually obtained only under conditions that significantly differ from the physiological ones and with ligands that are incompatible with the enzyme function, and both of these factors can inevitably influence the enzyme structure. Biochemical (such as mutagenesis, cleavage, and labeling) or spectroscopic experiments can yield only limited structural information, but this information could be considered relevant, because measurement can be performed under physiological conditions and with true ligands. However, interpretation of some biochemical or spectroscopic data could be difficult without precise knowledge of the structure. Thus, only a combination of both these approaches can extract the relevant information and identify artifacts. Briefly, there is good agreement between crystallographic and other experimental data concerning the overall shape of the molecule and the movement of cytoplasmic domains. On the contrary, the E1-AMPPCP crystallographic structure is, in details, in severe conflict with numerous spectroscopic experiments and probably does not represent the physiological state. Notably, the E1-ADP-AlF(4) structure is almost identical to the E1-AMPPCP, again suggesting that the structure is primarily determined by the crystal-growth conditions. The physiological relevance of the E2 and E2-P structures is also questionable, because the crystals were prepared in the presence of thapsigargin, which is known to be a very efficient inhibitor of SERCA. Thus, probably only crystals of E1-2Ca conformation could reflect some physiological state. Combination of biochemical, spectroscopic, and crystallographic data revealed amino acids that are responsible for the interaction with the nucleotide. High sequence homology of the P-type ATPases in the cytoplasmic domains enables prediction of the ATP-interacting amino acids also for other P-type ATPases.
Keywords: Plants; Models, Molecular; Protein Conformation; adenosintrifosfát; krystalografie rentgenová; Adenosine Triphosphatases; Adenosine Triphosphate; Animals; vazebná místa; Crystallography, X-Ray; zvířata; adenosintrifosfatasy; rostliny; molekulární modely; Binding Sites; konformace proteinů